The US Digital Presidential Election Campaigns (Donald Trump’s vs. Hillary Clinton’s) and their Impacts on Election Results of 2016 - boudis, naima; baghdadi, assia (Journal of Social Sciences and Humanities, 2024)
The 2016 American presidential election made the news world-wide for the popularity, or infamy thereof, of its final round candidates: Hilary Clinton and Donald J. Tramp. The use of social media as a communication channel and an advertisement tool in the 2016 election helped spread political messages and forge bridges between politicians and their respective constituents. Essentially, social media campaign ads were designed to remedy the out-of-touch elitist politics and dysfunctional aspects of the orthodox party-based campaigns that could no longer keep up with the changing culture. Nonetheless, social media political campaigns have been accorded hyperbolic power on a par with their effects on election results and shaping the public opinion. Thus, this article addresses the significance of digital political campaigns and probes the power of social media in determining the 2016 presidential election results and changing voters' decision.